Peningkatan Kinerja Guru SMA Negeri di Kota Kediri dalam Perspektif Ujian Nasional - Suwarno Suwarno; Sugeng Widodo; Teguh Pramono; Rizki Yudha Bramantyo (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2020)
The purposes of this study are to see teacher performance measured by the conduct of the national leaving exam in Kediri city. The study used a qualitative approach to which content analysis was done. For the in-depth analysis, observation and interviews were completed. After the data were collected, the trustworthiness of data was done by comparing various data. Data were analyzed using the interactive model proposed by Miles and Huberman (1984). Results show that to perform the national leaving exam, principals assigned teachers to well perform since the preparation of curriculum, teaching materials, teaching methods, and assessment tryout, to which the following well-prepared instructional designs were developed: enrichment of teaching materials, addition of teaching hours, learning guidance, tryout of national leaving exam, as well as guidance to mental and spiritual.